Informasi Anatomi dan Dosis Radiasi pada MSCT Brain Pediatric Menggunakan Adaptive Statistical Iterative Reconstruction (ASiR)-V - Indraratma, Fitri; Dartini, Dartini; Setiawan, Agung Nugroho (Jurnal Imejing Diagnostik (JImeD), 2023)
Background: Multislice CT Scan (MSCT) brain examination in pediatric cases should pay attention to the lowest possible dose but still provide optimal anatomical information. Pediatric has a higher risk of developing cancer compared to adults who receive the same dose. The purpose of this study is to obtain the optimal value of the use of the Adaptive Statistical Iterative Reconstruction (ASIR)-V technique with variations in tube current strength and Iterative Reconstruction value which is implemented in pediatric patients under the age of 5 (five) years. Methods: This research was experimental with brain image samples of pediatric patients at the Radiology Installation of RSUD dr. Moewardi Surakarta. The variations of the tube currents selected were 80, 100, and 165 mA with a combination of AR20, AR40, AR60, and AR80 variations. Anatomical information processed descriptively sourced from the assessment of 3 (three) radiologists who were experienced in assessing MSCT images. Meanwhile, the effect of tube current variation on radiation dose was tested using linear regression. Results: The results showed differences in anatomical information between the combinations of 165 mA-AR60 and 165 mA-AR80 "very clear", 165 mA-AR20 "clear", 80 mA-AR20 "fairly clear" and 100 mA-AR80 "less clear". There was an effect of strong variation of tube current on radiation dose with a regression coefficient value of 0.690. The estimated effective doses of the three tube current values were still below the national Dose Reference Level (DRL). Conclusions: It was concluded that there were differences in anatomical information on the MSCT brain pediatric examination with variations in tube current and ASiR-V, there was an effect of variations in mA on radiation dose and mA values and the optimal value of the combination of techniques studied is 80 mA and 20% Iterative Reconstruction.